2022
DOI: 10.1002/tesq.3102
|View full text |Cite
|
Sign up to set email alerts
|

It may also be our own fault to think so, to limit them before even trying’: Assuming Learner Limitations during Materials Design in English Language Teacher Education

Abstract: Whilst the scholarship into language teaching materials and into language teacher education has gained considerable vitality since the mid-90s, the intersection of both fields has remained largely disconnected from one another from a research perspective. Bridging this gap, this study explores how a group of Chilean preservice teachers of English learn to design language teaching materials towards the end of their teacher education course. Drawing on the sociocultural framework of Activity Theory and using qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Only a minority of parents believe that education is solely the school's responsibility and feel they are too busy with work to take on an educational role. Some parents lack the competence and abilities to effectively interact with instructors, apply appropriate educational methods, and collaborate in their child's education, which can lead to disruptions and interference (Carabantes & Paran, 2022). The level of individual participation influences the end outcomes according to participation theory (Ichdan et al, 2023).…”
Section: Correlation Analysismentioning
confidence: 99%
“…Only a minority of parents believe that education is solely the school's responsibility and feel they are too busy with work to take on an educational role. Some parents lack the competence and abilities to effectively interact with instructors, apply appropriate educational methods, and collaborate in their child's education, which can lead to disruptions and interference (Carabantes & Paran, 2022). The level of individual participation influences the end outcomes according to participation theory (Ichdan et al, 2023).…”
Section: Correlation Analysismentioning
confidence: 99%
“…Under this circumstance, researchers explored the process of materials adaptation, including teachers' understanding, evaluation, and design of the teaching materials (Hanifa & Yusra, 2023;Carabantes & Paran, 2022;Choppin, 2011). For instance, Hanifa and Yusra (2023) researched how materials adaptation proceeds and found that teachers' feeling-sharing with the materials is significant in facilitating their understanding of the difficulty level of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Masuhara (2022) highlighted the importance of assuming learner limitations while adapting materials. Students' needs are prioritized, from commercial coursebook adaptations catering to regional needs to teachers' behavior of adapting materials as a part of teaching strategies (Carabantes & Paran, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…While the literature review also underscored how researchers have explored learning materials developed by teachers, most of the studies focused on in‐service teachers (e.g., Choi & Lo, 2022; Howard & Major, 2004; Li et al, 2021; Yuniarti, 2019) and paid little attention to how preservice teachers developed materials (e.g., Carabantes & Paran, 2022; de Laurentiis Brandão, 2018; Sert & Li, 2017; Usta & Güntepe, 2017) or how teacher educators evaluated these materials. Still, the literature review did reveal that teachers often approached materials design by applying language materials development principles (e.g., Núñez et al, 2009; Ota et al, 2018).…”
Section: Introductionmentioning
confidence: 99%